2018
DOI: 10.1089/lap.2018.0160
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Cardiac Sympathetic Denervation: Adjunct Therapy for Secondary Prevention of Life-Threatening Ventricular Arrhythmias in Children

Abstract: Thoracoscopic CSD can be safely performed in the neonate and pediatric populations. When utilized with medication therapy, CSD is an effective adjunct in reducing ICD discharges and arrhythmias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Of these, nine patients (60%) were male, and six (40%) were female. Patients' median age was 14 years (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The patients' data are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, nine patients (60%) were male, and six (40%) were female. Patients' median age was 14 years (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The patients' data are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In cases where LCSD fails to hamper ventricular arrhythmias, an auxiliary treatment, RCSD, might be an alternative. Research has shown that RCSD lessens cardiac arrhythmia [16,17]. Lin et al [18] reported that three of the six patients had undergone previous LCSD but developed arrhythmia recurrence; RCSD after prior LCSD was effective in suppressing these arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Это было достигнуто либо нейронной аблацией, либо стимуляцией. Нейронная аблация как метод лечения аритмий хорошо зарекомендовала себя при таком заболевании, как синдром удлиненного интервала QT [51][52][53][54].…”
Section: вегетативная нервная система и нарушения ритма сердцаunclassified